Preparation method of oxygen-containing high-strength beta titanium alloy material

Through induction suspension smelting and traditional forging and rolling processes, combined with solid solution strengthening of oxygen elements, a multi-scale mixed crystal structure is formed, which solves the problem of plasticity of β-titanium alloys at high strength, and realizes a new type that combines high strength and high plasticity. Oxygen-containing β-titanium alloy material meets the needs of high-performance equipment.

CN119194138APending Publication Date: 2024-12-27BEIJING UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411310867.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The plasticity of existing beta titanium alloys decreases sharply when their strength exceeds 1300MPa, which limits its wider application potential, especially in high-performance equipment, which is difficult to meet the requirements of high strength and good plasticity.

Method used

Induction suspension smelting technology is used in combination with traditional forging and rolling processes, solid solution strengthening and multi-scale mixed crystal structure are achieved by introducing oxygen elements, improving the tensile strength and elongation of the alloy, and ensuring material performance and processing convenience.

Benefits of technology

A new oxygen-containing β-titanium alloy material with both high strength and high plasticity has been realized, with a tensile strength of more than 1460MPa and an elongation of between 8.5% and 8.7%, meeting the high performance requirements of modern equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005050638680000011
    Figure HDA0005050638680000011
  • Figure HDA0005050638680000012
    Figure HDA0005050638680000012
  • Figure HDA0005050638680000021
    Figure HDA0005050638680000021
Patent Text Reader

Abstract

The invention discloses a preparation method of an oxygen-containing high-strength beta titanium alloy material, and belongs to the technical field of titanium alloy material preparation. The invention surrounds a Ti-Mo-V-Cr-Fe-Al-O alloy substrate, wherein the content of O is 0-0.6% and is not equal to 0. The method comprises the following steps: (1) proportioning alloy components, smelting, and casting to a customized mold to form a cast ingot; (2) forging the cast ingot into a square billet by using a free forging technology, and further rolling the square billet into a plate with a required specification; and (3) the board is subjected to heat treatment to reach the expected mechanical performance index. A traditional processing technology is used, mass production of the oxygen-containing high-strength beta titanium alloy plate can be achieved, the oxygen-containing high-strength beta titanium alloy plate is characterized in that a multi-scale mixed crystal structure is adopted, the practical application potential of the alloy plate is improved, the prepared plate shows excellent tensile strength and high ductility, and the wide application value of the oxygen-containing high-strength beta titanium alloy plate in the field of high-performance materials is fully reflected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a novel oxygen-containing high-strength beta titanium alloy material, belonging to the field of titanium alloy materials. Background Art

[0002] Titanium alloy has excellent performance combination - low density (only 4.5g / cm 3 , about half of that of steel), excellent specific strength and excellent corrosion resistance, making it an indispensable key structural material in the fields of aerospace, cutting-edge weapons and deep-sea exploration. Titanium alloys achieve significant weight reduction while ensuring the maximum load-bearing performance of components, which is crucial for improving aircraft performance, enhancing weapon system capabilities and expanding the boundaries of deep-sea exploration. Given that titanium resources rank fourth in abundance in the earth's crust, following aluminum, iron and magnesium, they have great potential for large-scale application.

[0003] The development of high-strength β-titanium alloys, especially as an alternative to high-strength steel weight reduction, is a major breakthrough in materials science. From the pioneering development of Ti-13V-11Cr-3Al to the mature application of Ti-5Al-5Mo-5V-3Cr-1Zr, these materials have not only witnessed a significant improvement in strength and processing performance, but especially Ti-5Al-5Mo-5V-3Cr-1Zr, which has become an ideal choice for a new generation of high-strength fuselage components by virtue of its excellent heat treatment strengthening ability, high fracture toughness and good thermal stability. However, in the face of the rapid development of high-performance equipment, the performance limitations of existing β-titanium alloys are becoming increasingly apparent, especially the problem of a sharp drop in plasticity when the strength exceeds 1300MPa (can Example 1 overcome this), which limits its wider application potential. Therefore, the development of a new β-titanium alloy that can maintain both high strength and good plasticity has become the key to meeting the high-performance requirements of modern equipment and overcoming the problem of "strong plastic inversion". Summary of the invention

[0004] The present invention aims to solve the above problems and innovatively proposes a new preparation process for oxygen-containing high-strength β-titanium alloy materials. Combining induction suspension melting technology with traditional forging and rolling processes, the produced plates show excellent tensile strength and elongation, and have excellent comprehensive performance.

[0005] The technical solution of the present invention is: a novel method for preparing oxygen-containing high-strength β titanium alloy, which is characterized by utilizing the solid solution strengthening effect and strong α stability characteristics of oxygen elements to induce the formation of a multi-scale mixed crystal structure to ensure that the alloy has both strength and plasticity. This method can produce high-performance β titanium alloy through standard processes, achieving a perfect combination of material performance and processing convenience.

[0006] The composition (mass percentage) of the high-strength beta titanium alloy of the present invention is: Mo 3.5-4.5%, Cr 0.9-5%, V 2.5-3.5%, Fe 0.45-2.05%, Al 2.5-4.5%, O 0-0.6% and not 0, and the rest is Ti.

[0007] The preparation process is briefly described as follows:

[0008] (1) Ingredients: Select high-purity raw materials, including sponge titanium (99.5%), Al-Mo master alloy (99.5%), vanadium block (99.5%), high-purity chromium (99.9%), iron (99.9%), aluminum particles (99.9%) and titanium dioxide (99.5%) (titanium dioxide is used to adjust the oxygen content), and accurately weigh them according to a predetermined weight ratio; use a layered pressing method to form a blank in a mold to ensure that the lower part is a light material and the upper part is a heavy material, and the blank diameter is smaller than the crucible diameter; then, pre-treat in a drying oven at 80-120° C. for 40-80 minutes to completely remove residual moisture in the raw materials;

[0009] (2) Induction levitation melting: Place the billet into a vacuum induction levitation melting furnace (the vacuum degree is maintained at 2-4×10 -2 Pa, filled with argon for protection); initially preheated at 50KW, then adjusted to 170KW for full melting, and after melting, the power was adjusted back to 150KW to ensure that the melt was suspended and stirred for more than 90 seconds to improve the uniformity of the composition. To ensure the quality of the alloy, the smelting process was repeated three times; after the final smelting was completed, the molten metal was poured into a steel mold for casting to form a preliminary ingot. After removing the riser, a cylindrical finished ingot was obtained;

[0010] (3) Multi-directional free forging: Turning and cleaning step (2) Ingot surface defects. Subsequently, the box-type resistance furnace is heated to 850-1000℃, and the pre-treated ingot is kept warm for 60-80min; after heating, the ingot is quickly moved to the electro-hydraulic hammer for forging, ensuring that the deformation rate exceeds 20% each time, and the total deformation range is between 40%-60%. If the temperature is lower than 700℃ during this period, it needs to be returned to the furnace for 20-40min of insulation; after forging, it is naturally cooled by air to finally obtain a square billet;

[0011] (4) Rolling: After the forged billet in step (3) is cut and polished, the box-type resistance furnace is adjusted to 780-860°C and the billet is kept warm for 60-80 minutes. It is then quickly transferred to the rolling mill for rolling, with a deformation rate of 10% to 15% per pass. After each pass is rolled, it is returned to the furnace for insulation for 10-50 minutes, and the cumulative deformation rate is greater than 70%. After rolling is completed, air is also used for natural cooling to finally produce a rolled plate;

[0012] (5) Heat treatment: Samples of the rolled plate obtained in step (4) are subjected to solution heat treatment at 710-900°C for 40-80 min, followed by water quenching or air cooling; then, aging treatment is performed at 440-600°C for 8-12 h, followed by natural air cooling to room temperature.

[0013] In summary, the core advantages of the present invention are summarized as follows:

[0014] The present invention innovatively introduces a small amount of oxygen into the Ti-Mo-V-Cr-Fe-Al metastable β titanium alloy system, which not only achieves effective solid solution strengthening, but also promotes the α phase to present a multi-scale mixed crystal structure, and simultaneously enhances the strength and ductility of the alloy, achieving excellent comprehensive performance. Specifically, the combination of large-sized primary α phase and high aspect ratio secondary α improves strength, while small-sized primary α phase and low aspect ratio secondary α phase ensure plasticity. The alternating distribution of the two forms a microstructure with both high strength and high plasticity, laying a solid foundation for the further research and development of high-strength titanium alloys. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to further explain the features and objectives of the present invention, the following will be analyzed in detail with reference to the drawings and preferred embodiments, as follows:

[0016] Figure 1 The forging process flow of the Ti-Mo-V-Cr-Fe-Al-O alloy of the present invention in Example 1 is demonstrated, including the billet morphology before forging, a schematic diagram of the forging process, and the microstructure of the material before and after forging.

[0017] Figure 2 The microstructural characteristics of the heat-treated Ti-Mo-V-Cr-Fe-Al-O alloy rolled plate in Example 1 are presented.

[0018] Figure 3 The stress-strain curve of the Ti-Mo-V-Cr-Fe-Al-O alloy rolled plate in the heat-treated state in Example 1 is provided. DETAILED DESCRIPTION

[0019] The following content will further elaborate on the technical details of the present invention in conjunction with the accompanying drawings and specific embodiments. It should be pointed out that these descriptions are intended to provide assistance in understanding and are not intended to limit the scope of protection of the present invention. Any reasonable adjustment or equivalent substitution based on the technical solution of the present invention, as long as its core principles and effects do not deviate from the spirit and scope of the present invention, should be deemed to fall within the scope of protection of the present invention. For example, the embodiments may describe in detail a specific alloy component ratio, processing steps or heat treatment conditions, but this should not limit the application scenario or parameter selection of the present invention. As long as the modification or replacement means can achieve similar strengthening and plasticity optimization effects, or achieve other performance improvements that are not mentioned but consistent with the objectives of the present invention, they can be regarded as one of the protection contents of the present invention. Therefore, the true boundaries of the present invention are not limited to the specific operations listed in the text, but cover all variations and extensions that are in line with the intent of the invention and the basic principles.

[0020] Example 1, a novel oxygen-containing high-strength β-titanium alloy material, characterized by following the following specific steps: (1) The specific composition of the oxygen-containing high-strength β-titanium alloy is: Mo 4.0%, V 3.0%, Cr 4.0%, Fe 0.5%, Al

[0021] 3.5%, O 0.6%, and the rest is Ti. The alloy preparation starts with selected raw materials, including 99.5% sponge titanium, 99.5%

[0022] Al-Mo master alloy, 99.5% vanadium block, 99.9% high purity chromium, iron, aluminum particles and 99.5% titanium dioxide are accurately weighed according to the above ratios and pressed into the mold using the layered method to ensure that the light material is at the bottom and the heavy material is at the top, and the diameter of the billet is smaller than the crucible size.

[0023] Keep in a drying oven at 100°C for 60 minutes to fully remove the remaining moisture in the material.

[0024] (2) Induction levitation melting: The pressed billet is placed in a vacuum chamber with a degree of vacuum of 3.2×10 -2 Pa water-cooled copper crucible, protected by argon. In the initial stage of smelting, the power is preheated with 50KW, then increased to 170KW until completely melted, and then reduced to 150KW to maintain the melt suspension and stirring for 90 seconds to ensure uniform mixing. In order to ensure the accuracy and uniformity of the alloy composition, the entire smelting process is repeated three times. After the final round of smelting, the molten liquid is poured into a steel mold to complete the casting, the ingot is de-riserized, and finally a cylindrical finished ingot is obtained.

[0025] (3) Multi-directional free forging: First, the surface of the ingot is turned to eliminate casting defects. The box-type resistance furnace is heated to 950°C, and the treated ingot is kept warm for 60 minutes and then quickly moved to the electro-hydraulic hammer equipment for multi-directional free forging. The deformation rate of each hammer blow is 20%, and the cumulative deformation is 40%. If the billet temperature drops below 700°C during the forging process, it needs to be returned to the furnace for 30 minutes. After the forging operation is completed, it is cooled by natural air cooling to finally obtain a billet. A visual display of this process can be seen in Figure 1 , which includes the forging process of the alloy, the morphology of the billet after forging, and its microstructure.

[0026] (4) Rolling: The square billet obtained after forging in step (3) is first cut and polished. The temperature of the box-type resistance furnace is set to 780°C and preheated. After reaching the set temperature, the prepared square billet is placed in the furnace and kept warm for 60 minutes. Subsequently, the square billet is quickly taken out and sent to the rolling mill for rolling. The deformation amount of each pass is controlled at 12.5%, and after each rolling, it is returned to the furnace and kept warm for 10 minutes to ensure that the total deformation rate reaches 75%. After completing all the rolling steps, it is cooled by natural cooling to finally obtain a rolled plate.

[0027] (5) Heat treatment: a sample is cut from the rolled plate obtained in step (4), and subjected to a solution treatment at 870°C for 80 min, followed by rapid cooling by water quenching, followed by an aging treatment at 590°C for 10 h, and then naturally air-cooled to room temperature. Figure 2 The microstructure of Ti-Mo-V-Cr-Fe-Al-O alloy rolled plate after heat treatment is shown. Figure 3 The stress-strain curve of the alloy rolled plate under heat treatment was revealed, reflecting its mechanical properties - the tensile strength reached 1460MPa and the elongation was 8.7%.

[0028] Example 2, a novel oxygen-containing high-strength β-titanium alloy material, characterized by following the following specific steps: (1) The specific composition of the oxygen-containing high-strength β-titanium alloy is: Mo 4.0%, V 3.0%, Cr..0%, Fe 2.0%, Al 3.5%, O0.15%, and the rest is Ti. The alloy preparation starts with selected raw materials, including 99.5% sponge titanium, 99.5%

[0029] Al-Mo master alloy, 99.5% vanadium block, 99.9% high purity chromium, iron, aluminum particles and 99.5% titanium dioxide are accurately weighed according to the above ratios and pressed into the mold using the layered method to ensure that the light material is at the bottom and the heavy material is at the top, and the diameter of the billet is smaller than the crucible size.

[0030] Keep in a drying oven at 100°C for 60 minutes to fully remove the remaining moisture in the material.

[0031] (2) Induction levitation melting: The pressed billet is placed in a vacuum chamber with a degree of vacuum of 3.0×10 -2 Pa water-cooled copper crucible, protected by argon. In the initial stage of smelting, the power is preheated with 50KW, then increased to 170KW until completely melted, and then reduced to 150KW to maintain the melt suspension and stirring for 90 seconds to ensure uniform mixing. In order to ensure the accuracy and uniformity of the alloy composition, the entire smelting process is repeated three times. After the final round of smelting, the molten liquid is poured into a steel mold to complete the casting, the ingot is de-riserized, and finally a cylindrical finished ingot is obtained.

[0032] (3) Multi-directional free forging: First, the surface of the ingot is turned to eliminate casting defects. The box-type resistance furnace is heated to 950°C, and the treated ingot is kept warm for 60 minutes and then quickly moved to the electro-hydraulic hammer equipment for multi-directional free forging. The deformation rate of each hammering is 20%, and the cumulative deformation is 40%. If the billet temperature drops below 700°C during the forging process, it needs to be returned to the furnace for 30 minutes. After the forging operation is completed, it is cooled by natural air cooling to finally obtain a square billet.

[0033] (4) Rolling: The square billet obtained after forging in step (3) is first cut and polished. The temperature of the box-type resistance furnace is set to 850°C and preheated. After reaching the set temperature, the prepared square billet is placed in the furnace and kept warm for 60 minutes. Subsequently, the square billet is quickly taken out and sent to the rolling mill for rolling. The deformation amount of each pass is controlled at 10%, and after each rolling, it is returned to the furnace and kept warm for 10 minutes to ensure that the total deformation rate reaches 80%. After completing all the rolling steps, it is cooled by natural cooling to finally obtain a rolled plate.

[0034] (5) Heat treatment: A sample was cut from the rolled plate obtained in step (4), and solution treated at 820°C for 60 min, followed by natural air cooling. Then, an aging treatment was performed at 560°C for 8 h, followed by natural air cooling to room temperature. Mechanical property tests showed that the tensile strength reached 1503 MPa and the elongation was 8.5%.

Claims

1. A method for preparing an oxygen-containing high-strength β-titanium alloy material, characterized in that: The matrix is ​​a Ti-Mo-V-Cr-Fe-Al alloy, whose mass percentage components are: Mo 3.5-4.5%, Cr 0.9-5%, V 2.5-3.5%, Fe 0.45-2.05%, Al2.5-4.5%, O 0-0.6% and not 0, and the rest is Ti; The following steps are involved: (1) Ingredients: Select high-purity raw materials, including sponge titanium, Al-Mo master alloy, vanadium block, high-purity chromium (99.9%), iron, aluminum particles and titanium dioxide, and accurately weigh them according to a predetermined weight ratio; use a layered pressing method to form a blank in a mold to ensure that the lower part is a light material and the upper part is a heavy material, and the blank diameter is smaller than the crucible diameter; then, pre-treat in a drying oven at 80-120° C. for 40-80 minutes to completely remove residual moisture in the raw materials; (2) Induction levitation melting: The blank is placed in a water-cooled copper crucible in a vacuum induction levitation melting furnace. The vacuum degree of the melting furnace is maintained at 2-4×10 -2 Pa and filled with argon for protection, initially preheated at 50KW, then adjusted to 170KW for full melting, and after melting, the power was adjusted back to 150KW to ensure that the melt was suspended and stirred for more than 90 seconds to improve the uniformity of the composition; to ensure the quality of the alloy, the smelting process was repeated three times; after the final smelting was completed, the molten metal was poured into a steel mold for casting to form a preliminary ingot; after removing the riser, a cylindrical finished ingot was obtained; (3) Multi-directional free forging: Turning and cleaning step (2) of the ingot surface defects; then, the box-type resistance furnace is heated to 850-1000°C, and the pre-treated ingot is kept warm for 60-80 minutes; after heating, the ingot is quickly moved to the electro-hydraulic hammer for forging, ensuring that the deformation rate exceeds 20% each time and the total deformation range is between 40% and 60%. If the temperature is lower than 700°C during this period, it needs to be returned to the furnace for 20-40 minutes of insulation; after forging, it is naturally cooled by air to finally obtain a square billet; (4) Rolling: After the forged billet in step (3) is cut and polished, the box-type resistance furnace is adjusted to 780-860°C and the billet is kept warm for 60-80 minutes; then it is quickly transferred to the rolling mill for rolling, and the deformation rate of each pass is 10% to 15%. After each rolling, it is returned to the furnace for insulation for 10-50 minutes, and the cumulative deformation rate exceeds 70%; after rolling, it is also cooled naturally by air to finally produce a rolled plate; (5) Heat treatment: Samples of the rolled plate obtained in step (4) are subjected to solution heat treatment at 710-900°C for 40-80 min, followed by water quenching or air cooling; then, aging treatment is performed at 440-600°C for 8-12 h, followed by natural air cooling to room temperature.

2. The method for preparing an oxygen-containing high-strength β titanium alloy material according to claim 1, characterized in that: The purity of all raw materials in step (1) is above 99.5%.

3. The method for preparing an oxygen-containing high-strength β titanium alloy material according to claim 1, characterized in that: Step (3), heating the furnace to above 850°C, keeping the temperature for 60-80 minutes, forging temperature above 850°C, and deformation rate in each direction greater than 40%.

4. The method for preparing an oxygen-containing high-strength β-titanium alloy material according to claim 1, characterized in that: In step (4), the rolling temperature range is 780-860° C., the holding time is 1 hour, and the cumulative rolling deformation rate is greater than 70%.

5. An oxygen-containing high-strength β titanium alloy prepared according to the method described in any one of claims 1 to 4.